Electromyographic analysis of the pectoralis major and deltoideus anterior muscles in horizontal flyer exercises with loads - Rodrigues, José Antonio [UNESP]; Büll, M. L. [UNESP]; Dias, G. A R [UNESP]; Gonçalves, M. [UNESP]; Guazzelli, J. F. [UNESP] (My University, 2003)
The effective activity of the pectoralis major and deltoideus anterior muscles in horizontal flyer exercises with external loads of 25, 50, 75 and 100% of the maximum load was studied in 11 male volunteers. The electromyographic analysis was done by using MEDI-TRACE-200 surface electrodes connected to a biological signal acquisition mode coupled to a PC/AT computer. The electromyographic signals were processed and the values obtained were normalized through maximum voluntary isometric contraction. It was statistically observed that in all types and loads of this exercise, the muscles presented significant differences in the concentric and eccentric phases. In the concentric phase, when different loads were compared, the muscles were more active with 75 and 100% of the maximum load, while in the eccentric phase, higher activity was observed with 100% of the maximum load. By analyzing each load effect in the concentric phase, it was verified that the muscles on the left side were more active than those on the right side with 25, 75 and 100% of the maximum load.
Keywords: adult; arm exercise; computer system; controlled study; deltoid muscle; electrode; electromyography; exercise; human; human experiment; loading test; male; muscle action potential; muscle isometric contraction; normal human; pectoralis major muscle; signal processing; statistical analysis; Adolescent; Adult; Electromyography; Exercise; Humans; Isometric Contraction; Male; Pectoralis Muscles; Posture; Reference Values; Weight-Bearing